Music value and participation: An Australian case study of music provision and support in Early Childhood Education. (December 2018) - Barrett, Margaret S.; Flynn, Libby Maree; Welch, Graham F.
There is a growing body of evidence that early engagement in active music-making impacts beneficially on children's wider development. Recent research indicates that individual and shared music-making in family settings contributes to positive parenting practices and identity development in young children. Children who participate in shared music-making at age 3 are better prepared for school experiences at age 5. These findings suggest music should be a compulsory requirement in any early childhood programme. This article reports the findings of a case study investigation of the provision of music in an Australian Early Childhood Education Centre. Findings suggest that music provision is best supported when there is a high value for music amongst staff, there is a range of value-added as well as integrated uses of music, and there is sustained music professional development for all staff.